Cardioprotection Via Modulation of Calcium Homeostasis by Thiopental in Hypoxia-Reoxygenated Neonatal Rat Cardiomyocytes - Kim, Hyun-Soo (Yonsei University College of Medicine, 2010)
PURPOSE: Ca(2+) homeostasis plays an important role in myocardial cell injury induced by hypoxia-reoxygenation, and prevention of intracellular Ca(2+) overload is key to cardioprotection. Even though thiopental is a frequently used anesthetic agent, little is known about its cardioprotective effects, particulary in association with Ca(2+) homeostasis. We investigated whether thiopental protects cardiomyocytes against hypoxia-reoxygenation injury by regulating Ca(2+) homeostasis. MATERIALS AND METHODS: Neonatal rat cardiomyocytes were isolated. Cardiomyocytes were exposed to different concentrations of thiopental and immediately replaced in the hypoxic chamber to maintain hypoxia. After 1 hour of exposure, a culture dish was transferred to the CO(2) incubator and cells were incubated at 37℃ for 5 hours. At the end of the experiments, the authors assessed cell protection using immunoblot analysis and caspase activity. The mRNA of genes involved in Ca(2+) homeostasis, mitochondrial membrane potential, and cellular Ca(2+) levels were examined. RESULTS: In thiopental-treated cardiomyocytes, there was a decrease in expression of the proapoptotic protein Bax, caspase-3 activation, and intracellular Ca(2+) content. In addition, both enhancement of anti-apoptotic protein Bcl-2 and activation of Erk concerned with survival were shown. Furthermore, thiopental attenuated alterations of genes involving Ca(2+) regulation and significantly modulated abnormal changes of NCX and SERCA2a genes in hypoxia-reoxygenated neonatal cardiomyocytes. Thiopental suppressed disruption of mitochondrial membrane potential (ΔΨ(m)) induced by hypoxia-reoxygenation. CONCLUSION: Thiopental is likely to modulate expression of genes that regulate Ca(2+) homeostasis, which reduces apoptotic cell death and results in cardioprotection.